Temperature cycling with Peltier elements of boards with SMD components and failure evaluation. Issue 2 (1st April 2014) - Šandera, Josef; Nicák, Michal
Abstract : Purpose: – This article aims to discuss the construction of a system for temperature cycling, where Peltier elements are used as heating or cooling elements. This article describes the results and experiences based on several years of practice in the area of thermo-mechanical reliability of soldered joints on printed boards with SMD components. Design/methodology/approach: – The authors discuss the characteristics of the design, the threshold temperatures, dynamic properties of the system and, most importantly, the reliability and the useful life of the Peltier elements. The advantages and disadvantages of the system are mentioned as well as examples of use. Findings: – The utilisation of Peltier elements for temperature cycling is possible, but it is important to keep in mind that the reliability of the elements is similar to the reliability of the system, and therefore, it is essential to replace the defective Peltier elements during the cycling. Research limitations/implications: – The construction of system is very simply. It is necessary to ensure the Peltier elements with low dispersion parameters. Originality/value: – The system is very well suited for cycling of printed boards, especially one sided, multi-chip systems, COB systems, flip-chip embedded construction, etc. The system can be used in situations where it is possible to ensure an effective heat transfer and where extremely low temperatures are not required.